2013
DOI: 10.1021/jp408429v
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Selective Etching of PMMA Residues from Transferred Graphene by Carbon Dioxide

Abstract: During chemical-vapor-deposited graphene transfer onto target substrates, a polymer film coating is necessary to provide a mechanical support. However, the remaining polymer residues after organic solvent rinsing cannot be effectively removed by the empirical thermal annealing in vacuum or forming gas. Little progress has been achieved in the past years, for little is known about the chemical evolution of the polymer macromolecules and their interaction with the environment. Through in situ Raman and infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 36 publications
15
82
1
Order By: Relevance
“…As shown in Figure , the first treatment induced no relevant change to the G, 2D Raman bands apart from a small decrease of their intensity ratio from 2.8 down to 2.0. The successive vacuum treatment up to 18.5 h gives a blue shift of the two bands, some further reduction of their intensity ratio and the appearance of a large unresolved signal below the G band that can be associated to some amorphous carbon contribution arising from residual PMMA carbonization . The treatment of a sample in CO 2 atmosphere gives again minor changes to the positions of the Raman bands and a decrease of their intensity ratio down to 1.7.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure , the first treatment induced no relevant change to the G, 2D Raman bands apart from a small decrease of their intensity ratio from 2.8 down to 2.0. The successive vacuum treatment up to 18.5 h gives a blue shift of the two bands, some further reduction of their intensity ratio and the appearance of a large unresolved signal below the G band that can be associated to some amorphous carbon contribution arising from residual PMMA carbonization . The treatment of a sample in CO 2 atmosphere gives again minor changes to the positions of the Raman bands and a decrease of their intensity ratio down to 1.7.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, there have been many efforts to remove these PMMA residues by various techniques, among which thermal annealing in vacuum or inert gases are most widely applied. Nonetheless it has been reported that some PMMA residues still remain on the surface after thermal annealing, resulting in scattering and defects .…”
Section: Summary Of Test Results Of Electrical Characterization On Gfmentioning
confidence: 99%
“…Despite the good results discussed above, the most common procedure to remove resist residue (introduced during the fabrication process) from the contact areas is the thermal annealing [110,121,161,162]. Above 200°C the decomposition of the resist residues takes place [152,161], but if annealing is performed after the metal deposition of the contact electrodes, it is difficult that residues may be removed. Indeed, for Ni-contacted graphene it has been reported that there is no relevant improvement of contact resistance after thermal annealing performed on the already contacted device [162].…”
Section: Surface Treatmentsmentioning
confidence: 99%